The Brazilian version of the Neuropsychiatric Inventory-Clinician rating scale (NPI-C): Reliability and validity in dementia - Stella, Florindo [UNESP]; Forlenza, Orestes Vicente; Laks, Jerson; De Andrade, Larissa Pires [UNESP]; Avendaño, Michelle A. Ljubetic; Sé, Elisandra Villela Gasparetto; De Castilho Cação, João; Lyketsos, Constantine G.; De Medeiros, Kate (Elsevier, 2013)
ABSTRACT Background: Patients with dementia may be unable to describe their symptoms, and caregivers frequently suffer emotional burden that can interfere with judgment of the patient's behavior. The Neuropsychiatric Inventory-Clinician rating scale (NPI-C) was therefore developed as a comprehensive and versatile instrument to assess and accurately measure neuropsychiatric symptoms (NPS) in dementia, thereby using information from caregiver and patient interviews, and any other relevant available data. The present study is a follow-up to the original, cross-national NPI-C validation, evaluating the reliability and concurrent validity of the NPI-C in quantifying psychopathological symptoms in dementia in a large Brazilian cohort. Methods: Two blinded raters evaluated 312 participants (156 patient-knowledgeable informant dyads) using the NPI-C for a total of 624 observations in five Brazilian centers. Inter-rater reliability was determined through intraclass correlation coefficients for the NPI-C domains and the traditional NPI. Convergent validity included correlations of specific domains of the NPI-C with the Brief Psychiatric Rating Scale (BPRS), the Cohen-Mansfield Agitation Index (CMAI), the Cornell Scale for Depression in Dementia (CSDD), and the Apathy Inventory (AI). Results: Inter-rater reliability was strong for all NPI-C domains. There were high correlations between NPI-C/delusions and BPRS, NPI-C/apathy-indifference with the AI, NPI-C/depression-dysphoria with the CSDD, NPI-C/agitation with the CMAI, and NPI-C/aggression with the CMAI. There was moderate correlation between the NPI-C/aberrant vocalizations and CMAI and the NPI-C/hallucinations with the BPRS. Conclusion: The NPI-C is a comprehensive tool that provides accurate measurement of NPS in dementia with high concurrent validity and inter-rater reliability in the Brazilian setting. In addition to universal assessment, the NPI-C can be completed by individual domains. © International Psychogeriatric Association 2013.
Keywords: Alzheimer's disease; Brazil; dementia; neuropsychiatric assessment; neuropsychiatric symptoms; scale; aged; aggression; agitation; anxiety; apathy; appetite disorder; Brief Psychiatric Rating Scale; caregiver; caregiver burden; Clinical Dementia Rating; concurrent validity; convergent validity; Cornell Scale for Depression in Dementia; counseling; delusion; depression; dysphoria; eating disorder; euphoria; female; follow up; hallucination; human; interrater reliability; interview; irritability; major clinical study; male; measurement accuracy; Mini Mental State Examination; motor dysfunction; neuropsychiatric inventory clinician rating scale; personal experience; rating scale; sleep disorder; vocalization